The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ppl.12929
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐polymorphism of plant thylakoid membranes. Enhanced non‐bilayer lipid phases associated with increased membrane permeability

Abstract: Earlier experiments, using 31P‐NMR and time‐resolved merocyanine fluorescence spectroscopy, have shown that isolated intact, fully functional plant thylakoid membranes, in addition to the bilayer phase, contain three non‐bilayer (or non‐lamellar) lipid phases. It has also been shown that the lipid polymorphism of thylakoid membranes can be characterized by remarkable plasticity, i.e. by significant variations in 31P‐NMR signatures. However, changes in the lipid‐phase behaviour of thylakoids could not be assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
(62 reference statements)
3
20
0
Order By: Relevance
“…3). In our earlier study we have shown close correlation between the gradually enhanced isotropic lipid phases, accompanied by shifts of the 31 P-NMR isotropic peaks to higher field positions, and the increased permeability of thylakoid membranes 31 .…”
Section: Ph-dependent Changes In the Lipid Polymorphism And In The Mesupporting
confidence: 57%
See 2 more Smart Citations
“…3). In our earlier study we have shown close correlation between the gradually enhanced isotropic lipid phases, accompanied by shifts of the 31 P-NMR isotropic peaks to higher field positions, and the increased permeability of thylakoid membranes 31 .…”
Section: Ph-dependent Changes In the Lipid Polymorphism And In The Mesupporting
confidence: 57%
“…2b and Supplementary Fig. 2; see also 31 ); (2) the magnitude of the pH-induced shifts Figure 1. Measured and spectrally deconvoluted and fitted 31 P-NMR spectra of isolated spinach thylakoid membranes.…”
Section: Ph-dependent Changes In the Lipid Polymorphism And In The Mementioning
confidence: 99%
See 1 more Smart Citation
“…A number of articles treat regulatory aspects of photosystem II (Shevela et al ), the plastoquinone pool (Borisova‐Mubarakshina et al ), cytochrome c (Bernal‐Bayard et al ), redox regulation (Nikkanen et al ), photoacclimation (Hu et al ) and photorespiration (García‐Caledrón et al ). The growing interest in structural aspects is shown by articles on the dynamics of the thylakoid membrane (Solovchenko et al , Konert et al , Ughy et al ) and of specific proteins (Carius et al , Vojta and Fulgosi ), protein complexes (Kuthanová Trsková et al , Fedorov et al ) and the antenna (Albanese et al , Kuthanová Trsková et al 2019). An important tool for photosynthesis research is variable chlorophyll fluorescence, which is used to study photosystem II in isolated form, in thylakoid membranes as well as in vivo.…”
mentioning
confidence: 99%
“…and theoretical and experimental consideration on the water-splitting complex (Capone et al 2019, Yamaguchi et al 2019, Chatterjee et al 2019) and photosystem I (Santabarbara et al 2019a) to more integrated aspects of photosynthesis research (Buezo et al 2019, Hamdani et al 2019, Ptushenko and Ptushenko 2019, Hernández-Prieto et al 2019, Krieger-Liszkay et al 2019). A number of articles treat regulatory aspects of photosystem II (Shevela et al 2019), the plastoquinone pool (Borisova-Mubarakshina et al 2019), cytochrome c (Bernal-Bayard et al 2019), redox regulation (Nikkanen et al 2019), photoacclimation (Hu et al 2019) and photorespiration (García-Caledrón et al 2019).The growing interest in structural aspects is shown by articles on the dynamics of the thylakoid membrane(Solovchenko et al 2019, Konert et al 2019, Ughy et al 2019 and of specific proteins (Carius et al 2019, Vojta and Fulgosi 2019), protein complexes (Kuthanová Trsková et al 2019, Fedorov et al 2019) and the antenna (Albanese et al 2019, Kuthanová…”
mentioning
confidence: 99%